Internalization of Tolerance Values to Realize Harmony Between Religious People Through Ogoh-Ogoh and Takbir Around Parade Traditions in Wonosalam Jombang - Mustofa, Ali; Indana, Nurul (Proceedings of Annual Conference for Muslim Scholars, 2024)
The research is based on religious traditions joined by other religions. This is unique since the fact, there are various religions adherents, and they join and participate towards the parade of “ogoh-ogoh” and “takbir”. This research is aimed to describe tolerance and harmony between religious communities. The research used qualitative methods with a sociological and anthropological approach, the data was collected by interviews, observation and documentation. The analysis is descriptive. The results of the research was the majority of people were involved in the “ogoh-ogoh” and” takbir” parade, they tidied up the roads during the activity. All of society have high tolerance towards other people and always maintain harmony towards Hindu, Buddhist, Islam, Christian and so Javanese communities is able to live side by side without religious conflict. Even, the people like different traditions.